1981
DOI: 10.1007/bf00238371
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic spikes induced in fast pyramidal tract neurons by thalamic stimulation

Abstract: In deeply anesthetized cats the synaptic events induced in fast pyramidal tract cells (Pt cells) by ventrolateral (VL) stimulation were analyzed with intracellular recordings. In 40% of the fastest conducting Pt neurons it was found that VL stimulation induced fast depolarizing potentials (FPPs) with or without underlying excitatory postsynaptic potentials (EPSPs). These FPPs were all or non fast rising events lasting about 2 ms. They could be induced by brachium conjunctivum stimulation or they could also occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(7 citation statements)
references
References 13 publications
3
4
0
Order By: Relevance
“…14C). This is in agreement with previous intracellular studies of neocortical pyramidal cells in vivo and in vitro 5,9,30,52 where it was observed that synaptic stimuli can elicit dendritic spikes (reviewed in Ref. 66).…”
Section: Synaptically-evoked Spikessupporting
confidence: 93%
See 1 more Smart Citation
“…14C). This is in agreement with previous intracellular studies of neocortical pyramidal cells in vivo and in vitro 5,9,30,52 where it was observed that synaptic stimuli can elicit dendritic spikes (reviewed in Ref. 66).…”
Section: Synaptically-evoked Spikessupporting
confidence: 93%
“…However, the applicability of this model to other cell types was questioned when the first intradendritic recordings revealed that dendrites can sustain active electrogenesis. 33,34,63 In neocortical and hippocampal pyramidal neurons for instance, intracellular recordings revealed that dendritic spikes can be elicited by synaptic inputs 5,9,30,52 and that they can amplify synaptic inputs electrotonically distant from the soma to initiate APs. 5 Moreover, the proximal apical dendrites of pyramidal neurons were found to contain voltage-gated Ca 2+ and Na + conductances capable of generating current densities similar to those observed at the soma.…”
mentioning
confidence: 99%
“…These events are likely to be dendritic spikes that did not reach action potential threshold in the soma/axon region, similar to the fast prepotentials described by Spencer and Kandel (1961). Similar events were reported in intracellular recordings of neocortical pyramidal cells in vivo (Deschênes 1981).…”
Section: Firing Properties During Active Periodssupporting
confidence: 74%
“…Despite their differences in connectivity and function, the neurons in each of the regions of the thalamus examined appear to exhibit similar electrophysiological properties, including similarities in input resistance, time constant, and level of spontaneous activity. Furthermore, in several cases neurons exhibited fast spikelike events somewhat similar to the FPPs described in other preparations (Eccles et al, 1958;Deschenes, 1981; Kuno and Llinas, 1970;Llinas and Nicholson, 1971;Spencer and Kandel, 1961). These events do not appear to be synaptically mediated, since the rapid falling phase of the spike suggests that the event is active in nature; furthermore, their frequency of occurrence can be altered by direct polarization of the soma.…”
Section: Electrophysiological Propertiessupporting
confidence: 61%